Physico-Chemical Properties and Structure of Oligomycin SC-II, Produced by Streptomyces virginiae 17 - A. N. Danilenko; M. V. Bibikova; I. A. Spiridonova; N. E. Grammatikova; A. V. Katlinsky (Антибиотики и Химиотерапия, 2020)
Under the screening programme for antibiotics with antifungal and immunosuppressive activities, Streptomyces virginiae 17 producing an oligomycin complex was isolated. Separation of the complex by HPLC showed that it contained two components at a ratio of 8:2. The physico-chemical characteristics of the components were investigated. The structure of oligomycin was assessed by13C NMR and1H NMR.